Assessing congestion in acute heart failure using cardiac and lung ultrasound - a review. (1st February 2021) - Johannessen, Øyvind; Myhre, Peder L.; Omland, Torbjørn
ABSTRACT: Introduction : Acute heart failure (AHF) is one of the leading causes of hospital admissions and is characterized by systemic and pulmonary congestion, which often precedes the overt clinical signs and symptoms. Echocardiography in the management of chronic HF is well described; however, there are less evidence regarding echocardiography and lung ultrasound (LUS) in the acute setting. Areas covered : We have summarized current evidence regarding the use of echocardiography and LUS for assessing congestion in patients with AHF. We discuss the value and reliability of handheld/pocketsize ultrasound devices in AHF. Expert opinion : Echocardiography is an essential tool for the diagnostic work up in patients with AHF. No individual parameter reliably detects congestion, thus the physician must integrate several measurements from the right and left heart. Novel methods and advances in cardiac imaging and clinical chemistry make it possible to detect congestion at an early stage. LUS is particularly helpful in assessing congestion, and it has demonstrated diagnostic, therapeutic, and prognostic value in AHF. LUS is relatively easy to learn and allows for quick assessment of the presence of pulmonary congestion and pleural effusion. We recommend integration of LUS for routine management of patients with AHF.